Management Updates In Acute Otitis Media Among Children: A Systematic Review - Maryam AwadAllah Alkhormani , Sahar Ghazi Almatrafi , Kholoud Salem Aljayzani , Fatimah Mohammed Zabbani, Salma moteb Almutairi , Faisal Mohammed Alshoudri (Supervisor) (Migration Letters, 2023)
Background: Over 60% of children will have experienced at least one episode of acute otitis media (AOM) by the time they are 4 years old, making it one of the most frequent illnesses in children. This study aimed to highlight the latest updates on otitis media management among children. Methods: This systematic review included randomized controlled trials, quasi-RCTs, and controlled before-and-after studies evaluating management updates in the treatment of acute otitis media (AOM) in children aged 0 to 18 years. The interventions evaluated included antibiotics, analgesics, and other supportive therapies, compared to placebo, standard care, or other active interventions. The primary outcomes were resolution of symptoms and [1]occurrence of complications, while secondary outcomes included adverse events, recurrence of AOM, and healthcare resource utilization. A comprehensive search of electronic databases was conducted, and data was extracted independently by two reviewers using a standardized form. Results: The study identified 398 publications through titles and abstracts, with eligibility determined for 11 publications through full-text review. Six studies were included, reporting on 1,862 patients. Antibiotic therapy was found to significantly reduce pain in children with acute otitis media compared to placebo, with a reduced incidence of contralateral otitis media and tympanic membrane perforation. However, there was no significant difference in tympanometry results between the antibiotic and control groups. The studies had low to moderate risk of bias and were conducted in the United States, Finland, Sweden, and Canada. Overall, the findings suggest that antibiotic therapy is effective in treating acute otitis media in children. Conclusion: The findings of this study suggest that antibiotic therapy is effective in reducing pain and decreasing the incidence of contralateral otitis media and tympanic membrane perforation in children with acute otitis media compared to placebo. However, there was no significant difference in tympanometry results between the antibiotic and control groups. The studies had low to moderate risk of bias and were conducted in various countries. The results support the use of antibiotic therapy in the treatment of acute otitis media in children.